2019
DOI: 10.14814/phy2.13992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenosine on short-term synaptic plasticity in mouse piriform cortex in vitro: adenosine acts as a high-pass filter

Abstract: We examined the effect of adenosine and of adenosine A1 receptor blockage on short‐term synaptic plasticity in slices of adult mouse anterior piriform cortex maintained in vitro in an in vivo‐like ACSF. Extracellular recording of postsynaptic responses was performed in layer 1a while repeated electrical stimulation (5‐pulse‐trains, frequency between 3.125 and 100 Hz) was applied to the lateral olfactory tract. Our stimulation protocol was aimed at covering the frequency range of oscillatory activities observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 126 publications
(189 reference statements)
1
17
0
Order By: Relevance
“…Exogenous adenosine can also be used to increase the adenosine concentration, Yuan et al found that the effect of preconditioning with adenosine on brain ischemic tolerance in rats. Perrier et al think that the main effects of adenosine were to decrease neurotransmitter release probability and to attenuate short‐term depression mechanisms. But this use is relatively rare, and it needs to be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous adenosine can also be used to increase the adenosine concentration, Yuan et al found that the effect of preconditioning with adenosine on brain ischemic tolerance in rats. Perrier et al think that the main effects of adenosine were to decrease neurotransmitter release probability and to attenuate short‐term depression mechanisms. But this use is relatively rare, and it needs to be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of A 1 receptors and ecto 5′-nucleotidases has been found in the piriform cortex, pointing to a role of adenosine in neuromodulation (Goodman and Synder, 1982; Trieu et al, 2015). The main targets of adenosinergic modulation in the piriform cortex are excitatory synaptic inputs in pyramidal cell dendrites (Rezvani et al, 2007; Yang et al, 2007; Trieu et al, 2015; Perrier et al, 2019). The somata of pyramidal cells reside in layer II/III of the piriform cortex, while their apical dendritic arbors extend into the superficial layer I (Figure 5B).…”
Section: Purinergic Signaling In the Olfactory Cortexmentioning
confidence: 99%
“…The low ambient adenosine concentration at layer Ib synapses results from slow ATP-to-adenosine conversion due to low abundance of ecto 5′-nucleotidase and lack of synaptic ensheathment by glial cell processes, which provide one major source of ATP in the cortex (Haberly and Behan, 1983; Nevill and Haberly, 2004; Pankratov and Lalo, 2015; Trieu et al, 2015; Yi et al, 2017). Synapses between lateral olfactory tract fibers and pyramidal cell dendrites in layer Ia are not only depressed by adenosine, but can also be facilitated dependent on the frequency of synaptic activation (Perrier et al, 2019). While adenosine has no effect on the amplitude of fEPSP evoked by a train of stimuli at frequencies between 3 and 25 Hz, it strongly facilitates fEPSP at frequencies between 50 and 100 Hz (Perrier et al, 2019).…”
Section: Purinergic Signaling In the Olfactory Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal circumstances, extracellular adenosine, a byproduct of neuronal ATP-driven vesicle release, establishes an inhibitory tone on synaptic terminals expressing the A1 adenosine receptor and provides negative feedback to active synapses. 10 Interestingly, when the authors delivered an adenosine receptor antagonist to sprouted mossy fiber slices from the brains of epileptic mice, they saw no effect on the evoked postsynaptic current. Thus, they concluded that the sprouted mossy fiber synapse lacks the normal inhibitory tone mediated by adenosine, thereby enabling a higher release probability.…”
Section: Commentarymentioning
confidence: 99%